The Impact of Sustainability Reporting and Digital Accounting Systems on the Financial Performance of Corporations - Muliawan, Adi; Fitri, Salsabila Dwi; Putra, Heldy Eka (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
This article examines the impact of sustainability reporting and digital accounting systems on corporate financial performance. Through a systematic review of current literature, it is found that transparent sustainability reporting and adoption of digital accounting technology can improve operational efficiency and investor confidence, which ultimately have a positive impact on corporate financial performance. However, challenges such as implementation costs and regulatory uncertainty remain obstacles to the implementation of both aspects. This article also details findings from various journals that highlight the positive relationship between sustainability reporting and financial performance, as well as the tangible benefits of digital accounting systems in strategic decision making. This study provides a solid foundation for the development of an integrative model between sustainability and digitalization in corporate accounting practices.